Eine diskursanalytische Betrachtung des rok-samizdat in der Sowjetunion und ihren Nachfolgestaaten in der Periode zwischen 1967 und 1994 - Bergmann, Martin (Slavistische Beitraege, 1999)
In the present work, the phenomenon of roc - samizdat in the Soviet Union and its successor states in the period between 1967 and 1994 is considered in terms of discourse analysis. In the first part of the thesis the used discourse analytical instruments are presented, in the second part the same is applied to selected texts. The rok-samizdat represents a form of samizdat, which, as will be shown in the present work, is thematically focused on the field of (rock) music.